Development of Flipbook-Based Mathematics E-Module on Trigonometric Comparison Material Class X of Senior High School 11 Pangkep - Rusli, R; Talib, Ahmad; Musa, Hastuty; Syahid, Nurul Khatimah; Rahman, Abdul (PT ARRUS Intelektual Indonesia, 2024)
This study aims to develop and produce a valid and feasible flipbook-based e-module for learning trigonometry comparisons, as well as to assess the quality of the e-module usage in terms of practicality and validity. This research was conducted at Senior High School 11 Pangkep. The research method refers to the 4D development model, which consists of four stages: Define, Design, Develop, and Disseminate. The subjects of this research were one mathematics teacher from the tenth grade of Senior High School 11 Pangkep, a subject matter expert, a media expert, and 35 tenth-grade students from Senior High School 11 Pangkep. The development research began with the define stage, conducted through literature review or preliminary research and field studies as a needs analysis to define the requirements for e-module development. The design stage included compilation, design, and format determination. The develop stage involved the development of the flipbook using the Heyzine platform and included validation by subject matter experts and media experts. Furthermore, the dissemination stage was limited to Senior High School 11 Pangkep in the tenth grade of Ki Hajar Dewantara class with a limited trial. The research instruments used in this study included e-module validation sheets by subject matter experts and media experts, teacher response questionnaires, and student response questionnaires. The results showed that the e-module is valid based on the assessment by subject matter experts with a score of 3.71 and by media experts with a score of 3.58, which are within the valid criteria, and practical based on very positive responses from students and teachers, with a score of 3.55 for student responses and a score of 3.85 for teacher responses.